Log in and breathe out: internet-based recovery training for sleepless employees with work-related strain - results of a randomized controlled trial - Hanne Thiart; Dirk Lehr; David Daniel Ebert; Matthias Berking; Heleen Riper (Nordic Association of Occupational Safety and Health (NOROSH), 2015)
OBJECTIVES: The primary purpose of this randomized controlled trial (RCT) was to evaluate the efficacy of a guided internet-based recovery training for employees who suffer from both work-related strain and sleep problems (GET.ON Recovery). The recovery training consisted of six lessons, employing well-established methods from cognitive behavioral therapy for insomnia (CBT-I) such as sleep restriction, stimulus control, and hygiene interventions as well as techniques targeted at reducing rumination and promoting recreational activities. METHODS: In a two-arm RCT (N=128), the effects of GET.ON Recovery were compared to a waitlist-control condition (WLC) on the basis of intention-to-treat analyses. German teachers with clinical insomnia complaints (Insomnia Severity Index ≥15) and work-related rumination (Irritation Scale, cognitive irritation subscale ≥15) were included. The primary outcome measure was insomnia severity. RESULTS: Analyses of covariance (ANCOVA) revealed that, compared to the WLC, insomnia severity of the intervention group decreased significantly stronger (F=74.11, P<0.001) with a d=1.45 [95% confidence interval (95% CI) 1.06-1.84] The number needed to treat (NNT) was <2 for reliable change and NNT <4 for reduction in expert-rated diagnosis of primary insomnia. CONCLUSION: The training significantly reduces sleep problems and fosters mental detachment from work and recreational behavior among adult stressed employees at post-test and 6-months follow up. Given the low threshold access this training could reach out to a large group of stressed employees when results are replicated in other studies.